Analisis Aspek Ergonomi pada Prototipe Alat Peraga Pendidikan Batang Truss untuk Mata Kuliah Kekuatan Material - Nia N. Permata; Royandi, Muhamad Aditya; Yessa F. Giantoyo; Asep Indra Komara; Muhammad Abdurrahman; Fadhlin Rizki (Badan Kerja Sama Teknik Mesin Indonesia, 2025)
Educational aids are very helpful in improving students' understanding of abstract subjects such as exact sciences. The Strength of Materials (SOM) course in the Manufacturing Design Engineering Department is supported by practical activities in the SOM studio using teaching aids, including truss bar tests. However, the currently used teaching aids have been complained about by students due to their complexity. Therefore, the development of a more user-friendly truss teaching aid prototype is needed. This article focuses on the evaluation of the impact of the developed teaching aid on its suitability for use in easier operations. The method used is observation techniques and interviews with students who have tried the previous teaching aids and the prototype being developed. The results showed that the prototype developed was better than the previous tool, because the procedure for using the tool was simpler and the duration of disassembling and assembling the test specimens was faster. Thus, it can be stated that the developed truss test teaching aid prototype is easier for students to use than the previous tool used in the SOM studio. Therefore, the development process and performance tracking of the developed prototype can be carried out at the next development stage.